2013
DOI: 10.1016/j.jchf.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Placement of an Intra-Aortic Balloon Pump in the Left Axillary/Subclavian Position Provides Safe, Ambulatory Long-Term Support as Bridge to Heart Transplantation

Abstract: Percutaneous insertion of an IABP through the left axillary artery is a feasible and relatively well-tolerated strategy to bridge patients with end-stage heart failure to heart transplantation. This form of mechanical-device treatment permits upright sitting and ambulation in those requiring extended support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(104 citation statements)
references
References 17 publications
4
96
0
4
Order By: Relevance
“…Bleeding at the insertion site was observed in 4% (n = 2) of the patients and was treated by stopping and or decreasing the heparin infusion dose (see Table 2). No data were gathered on malposition/exchange of the PAxIABP catheter owing to incomplete charting, although increased incidence of IABP catheter malposition was reported by Estep, 2013. [15] Notable problems encountered during ambulation were 1 episode of IABP console shutdown (the console was plugged in at the nearest wall outlet) and 1 episode of ventricular tachycardia without loss of conciousness that resolved spontaneously.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bleeding at the insertion site was observed in 4% (n = 2) of the patients and was treated by stopping and or decreasing the heparin infusion dose (see Table 2). No data were gathered on malposition/exchange of the PAxIABP catheter owing to incomplete charting, although increased incidence of IABP catheter malposition was reported by Estep, 2013. [15] Notable problems encountered during ambulation were 1 episode of IABP console shutdown (the console was plugged in at the nearest wall outlet) and 1 episode of ventricular tachycardia without loss of conciousness that resolved spontaneously.…”
Section: Complicationsmentioning
confidence: 99%
“…This procedure is done with a direct axillary artery percutaneous stick using a J wire guide inserted into the left brachial artery or femoral artery into the axillarysubclavian artery as a roadmap. [15] A regular intraaortic balloon pump catheter and console is used. The sheath and IABP catheter are sutured in place, secured with stat lock at the hub, and dressed with Tegaderm CHG (3M).…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous placement of IABP in axillary/subclavian position has been described as a bridge to heart transplantation 4. However, this technique requires major vascular intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The axillary and transaortic routes have been cited as alternatives in case reports, but these frequently require surgical intervention 2 3. A case of percutaneously placed axillary IABP has been described 4. We describe a case of a percutaneously placed IABP via the brachial approach.…”
Section: Introductionmentioning
confidence: 95%
“…The mean SBP was 103 mm Hg, with an average cardiac index of 2.1 L/min/m 2 . Median time of support was 18 days (range 4-152), with evidence of improvement in certain markers of end-organ function and hemodynamics [12]. In a single center retrospective study including 54 ADHF patients, Sintek et al [13] demonstrated that IABP prior to implantation of a left ventricular assist device led to clinical stability, without significant difference in mortality between those stabilized from those who decompensated.…”
Section: Figmentioning
confidence: 99%